EyeLncDB: A curated database of human long non-coding RNAs related to eye diseases - Meshkin, Alireza; Pournoor, Ehsan (Journal of Ophthalmic and Optometric Sciences, 2021)
Background: Eye diseases (EDs) are disorders of the ocular system, causing visual damage and sightlessness. Different studies have specified a wide range of biological functions of LncRNAs; consequently, their dysfunction directs to several diseases such as EDs. Growing evidence suggests that LncRNAs might be a new class of molecules for disease diagnosis and treatment in the future. Due to the importance and the detection of a large number of LncRNAs, genome-wide analyses are essential to identify which LncRNAs are associated with different diseases. For this purpose, it is vital to collect experimentally validated LncRNAs and predict novel LncRNAs associated with various eye diseases in a systematic manner. Material and methods: In the present study, researchers attempted to expand the current data using a powerful bioinformatics pipeline. We integrated the different resources of eye-related LncRNA information to provide a customized entry point for LncRNA-target research. Results: As a result, 429 mRNAs related to 25 humans EDs were identified, and 151 new experimentally validated physical interactions associated with these mRNA were identified. Finally, after organizing all the identified LncRNAs, respectively, 1038 and 89 experimentally validated and predicted LncRNAs were obtained. Conclusion: Here, we propose EyeLncDB (http://eyelncedb.databanks.behrc.ir/), a web-based platform of eye-related validated LncRNA data that contains the mentioned integrated information. EyeLncDB provides information on LncRNA-related diseases, pathways, genes, and targets with external links to the original data sources.